America again [compact disc, unabridged] : re-becoming the greatness we never weren't - Colbert, Stephen, 1964- (Hachette Audio, 2012)
In the history of mankind there has never been a greater country than America. But as perfect as America is in every single way, America is broken! It's high time America was restored to the greatness it never lost! Stephen Colbert single-bookedly attempts to pull the country back from the brink. Covering subjects ranging from healthcare to the economy to food, Stephen gives America the dose of truth it needs to get back on track.